The Influence of Discipline, Leadership and Motivation on Employee Performance at PT. BPR Jero Anom Tabanan - RINI, Febry Puspa; PUTRA, I.B. Udayana; SARI, Ni Made Taman (Journal of Social Sciences and Cultural Study, 2024)
This research aims to test and analyze the influence of work discipline, leadership style and work motivation on employee performance. This research was conducted at PT. BPR Jero Anom Tabanan, with a research sample of 34 respondents taken using saturated sampling techniques. All data obtained from the questionnaire distribution is suitable for use and is then analyzed using multiple linear regression and hypothesis testing (t-test and f-test). The research results show that (1) Work discipline, leadership style and work motivation positively and significantly affect employee performance at PT. BPR Jero Anom Tabanan (2) Work discipline positively and significantly affects employee performance at PT. BPR Jero Anom Tabanan. It means that the more work discipline increases, the more employee performance at PT will increase. BPR Jero Anom Tabanan's. (3) Leadership style positively and significantly affects employee performance at PT. BPR Jero Anom Tabanan. It means that the better the leadership style, the greater the employee performance at PT. BPR Jero Anom Tabanan. (4) Work motivation positively and significantly affects employee performance at PT. BPR Jero Anom Tabanan. It means that the more work motivation increases, the more employee performance at PT will increase. BPR Jero Anom Tabanan.